2014
DOI: 10.1093/arclin/acu047
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychological Functioning in Fabry Disease

Abstract: Fabry disease is an X-linked lysosomal storage disorder which can result in renal, cardiac, and cerebrovascular disease. Patients are at increased risk of stroke and neuroimaging studies note cerebrovascular pathology. This study provides a cognitive profile of a cohort of individuals with Fabry disease and investigates the impact of pain, age, renal, cardiac, and cerebrovascular functioning on cognition and psychological functioning. Seventeen Fabry patients (12 males) with ages ranging 25 to 60 years (M = 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 30 publications
6
42
4
1
Order By: Relevance
“…Of note, we could not confirm the previously observed relation [8] between a history of stroke and depressive symptoms, nor was there a relation between WMLs and depressive symptoms. This further strengthens the hypothesis that brain abnormalities are not the main cause of depressive symptoms in patients with FD [3,5].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Of note, we could not confirm the previously observed relation [8] between a history of stroke and depressive symptoms, nor was there a relation between WMLs and depressive symptoms. This further strengthens the hypothesis that brain abnormalities are not the main cause of depressive symptoms in patients with FD [3,5].…”
Section: Discussioncontrasting
confidence: 99%
“…It has been hypothesized that the cerebral pathology in FD might be a biological substrate for depressive symptoms [3,6,7]. Interestingly, while most studies failed to establish a relation between organ involvement and depressive symptoms [5,8], FD patients' perception of their health was strongly related to depressive symptom severity [4,9]. This relationship is not unique for FD and has been shown in other diseases as well [10].…”
Section: Introductionmentioning
confidence: 96%
“…The assessment of cognitive function in FD patients so far mostly revealed mild and unprogressive symptoms [4, 6, 7]. The lack of genotype differences in learning behavior of our FD mouse model is therefore in line with findings in Fabry patients.…”
Section: Discussionsupporting
confidence: 83%
“…Löhle et al (2015) found that antidepressants were more frequent among FD subjects than controls. Finally, FD does not follow gender norms, with males reporting greater depression than females (Cole et al 2007;Sigmundsdottier et al 2014).…”
Section: Introductionmentioning
confidence: 91%